2021
DOI: 10.1111/acel.13455
|View full text |Cite|
|
Sign up to set email alerts
|

Synaptic dysregulation and hyperexcitability induced by intracellular amyloid beta oligomers

Abstract: This is an open access article under the terms of the Creative Commons AttributionLicense, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 139 publications
(186 reference statements)
2
11
0
Order By: Relevance
“…Our results also suggest that changes in neuronal excitability might be occurring during the postsynaptic recordings, as evidenced by the higher number of recorded voltageclamped spikes as the concentration of αSynO increased. In fact, the effects described for intracellular αSynO regarding the frequency, amplitude, charge transferred, and increased number of voltage-clamped recorded spikes in the recordings are remarkably similar to those described for intracellular Aβ oligomers (Aβo) in a previous study by our laboratory [52]. Contrary to our findings, Yamamoto et al reported that the intracellular diffusion of a solution containing stable higher-order αSynO (larger than 100 kDa) decreased neuronal excitability [16].…”
Section: Intracellular Effects Of αSyno In Synaptic Physiologysupporting
confidence: 89%
See 1 more Smart Citation
“…Our results also suggest that changes in neuronal excitability might be occurring during the postsynaptic recordings, as evidenced by the higher number of recorded voltageclamped spikes as the concentration of αSynO increased. In fact, the effects described for intracellular αSynO regarding the frequency, amplitude, charge transferred, and increased number of voltage-clamped recorded spikes in the recordings are remarkably similar to those described for intracellular Aβ oligomers (Aβo) in a previous study by our laboratory [52]. Contrary to our findings, Yamamoto et al reported that the intracellular diffusion of a solution containing stable higher-order αSynO (larger than 100 kDa) decreased neuronal excitability [16].…”
Section: Intracellular Effects Of αSyno In Synaptic Physiologysupporting
confidence: 89%
“…The synaptic currents were analyzed as previously described [52]. Briefly, miniature postsynaptic current (mPSCs) frequency and amplitude were analyzed using the Mini analysis software (Synaptosoft, Inc., Leonia, NJ, USA).…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…APP transgenic mice evidently reveal deficits in learning and memory, behavioral abnormalities, synaptic alterations, and SPs [ 25 ]. Intracellular Aβ oligomers can affect normal transmission, increase neuronal excitability of hippocampal neurons, and cause synaptic damage [ 26 ]. Mitochondria-associated membranes are an intracellular site of APP processing and Aβ is produced at mitochondria-endoplasmic reticulum contact sites, which may contribute to AD pathology [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the actions of Aβ on synapses are reportedly mediated by PKCα through scaffold interactions (Alfonso et al, 2016 ). In the initial stages of AD, accumulated intracellular amyloid-beta oligomer causes functional spreading of hyperexcitability through a synaptic-driven mechanism, which is PKC-dependent (Fernandez-Perez et al, 2021 ). Significant suppression of PKCα activity was observed in the wild-type and 3×Tg-AD mice in the aged or postsurgical hippocampus.…”
Section: Discussionmentioning
confidence: 99%